SOURCES OF INFORMATION, LOCATION AND REPUTATION OF A UNIVERSITY CENTER - KEY FACTORS FOR DECISION-MAKING TO BE TRAINED AS A PHYSICAL THERAPIST AT "VASILE ALECSANDRI" UNIVERSITY OF BACAU - Dan Iulian ALEXE; Gabriel MAREȘ; Daniela CRĂCIUN (Editura Universităţii din Oradea, 2018)
Career orientation, factor analysis in making a decision, but also sometimes strong indecision in making a final decision, can constitute complex aspects of a process involving completely the person envisaging a professional career in a particular field.Making a decision involves a previous accumulation of information, but it also depends on less controllable factors (social, financial, material). This study aimed to analyze a series of aspects concerning the influences of various factors, influences that made 92 candidates choose to train professionally as physical therapists at the "Vasile Alecsandri" University of Bacau, during the main admissions in the summer of 2016. The candidates' opinions were collected using a 12-item questionnaire. This was administered before the admission examination.It can be concluded that at the "Vasile Alecsandri" University of Bacau, in making the decision, the candidates who chose to train as physical therapists, the influence of the human factor is significant in the finalization of the orientation process.